Book Review: The Silk Road in Anatolia, Roads and Caravanserai in the 16th and 17th Centuries - Rahman, Fathan Aulia (Islamic Social Finance, 2025)
The book Anadolu’da İpek Yolu XI–XIV. Yüzyıllarda Yollar ve Kervansaray by Ali Kilci and Gökçe Günel is a historical-visual study that discusses the role of the Silk Road in the Anatolia region during the Middle Ages, specifically between the 11th and 14th centuries. Published by the General Directorate of Foundations under the Turkish Ministry of Tourism and Culture, this book highlights the close relationship between international trade networks and the development of waqf (foundation) institutions in Turkish history. The first part of the book explains the Silk Road routes that traversed important cities such as Erzurum, Sivas, Kayseri, Konya, Antalya, Bursa, and Istanbul, emphasizing its role in bringing together the Eastern and Western worlds. The second part details the strategic function of the kervansaray—caravanserais built and managed through the waqf system—as economic, social, and philanthropic infrastructures that guaranteed the safety, comfort, and continuity of trade along these routes. This book also displays the architectural and cultural dimensions of the kervansaray as a symbol of public service open to all, regardless of origin or background. Although not compiled with a deep academic approach, this work is highly valuable as an educational tool introducing the historical and cultural heritage of the Silk Road in Anatolia, as well as being an inspiring source for understanding the relationship between foundations, trade, and civilizational development during the Seljuk period.